Peningkatan Motivasi Belajar Dengan Pendekatan Bermain Pada Pelajaran PJOK Kelas III: Penelitian - Jordan Agung Mubarak; Ardhi Mardiyanto Indra Purnomo; Mohammad Yunan Firmansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to find out whether the play approach can increase students' learning motivation In Physical Education (PE) learning, many students lack enthusiasm in participating in learning because learning is boring and uninteresting. The play method may be very effective because elementary school students aged 9-12 years old usually love to play. Children are generally more interested in fun activities, such as playing. These activities not only attract their attention, but also help in cognitive and social development. Additionally, playing can be an important means of learning to overcome challenges and interact with peers. By giving them the opportunity to play, we support their learning process in a playful atmosphere. This can encourage them to exercise and stay healthy and fit. PTK is carried out in 2 cycles with two meetings that discuss the topic of physical fitness. To evaluate students' perspectives on the learning carried out, data was collected through observation, documentation, and questionnaires. Research shows that the play method can greatly increase students' motivation to learn PE in grade III of SDN Bawang Kota Kediri.